Exosomes Derived From Macrophages Enhance Aerobic Glycolysis and Chemoresistance in Lung Cancer by Stabilizing c-Myc via the Inhibition of NEDD4L - Wang, Huan; Wang, Lie; Pan, Haiyan; Wang, Yaona; Shi, Miao; Yu, Hang; Wang, Chaoye; Pan, Xinfu; Chen, Zhijun (Frontiers in Cell and Developmental Biology, 2021)
As one of the most common and lethal cancer, lung cancer severely threatens the health of human. It has been reported that tumor-associated macrophages promote initiation, progression, as well as chemoresistance in human cancers. However, the underneath molecular mechanism that drives chemoresistance in lung cancer is yet not fully characterized. In this article, we demonstrated that M2 macrophage-derived exosomes (MDE) is the key factor to promote cisplatin-resistance in lung cancer. MDE exhibited high expression level of several miRNA including miR-3679-5p. Mechanistically, miR-3679-5p was delivered to lung cancer cells by MDE, downregulating the expression of a known E3 ligase, NEDD4L, which has been identified as a key regulator controlling the stability of c-Myc. Such decreased NEDD4L expression level resulted in the stabilization of c-Myc and elevated glycolysis. The enhanced glycolysis drives the chemoresistance in lung cancer. Taken together, our findings not only show that M2 macrophage induce chemoresistance in lung cancer through MDE mediated miR-3679-5R/NEDD4L/c-Myc signaling cascade, but also shed the light on the mechanism of the cross-talk between M2 macrophage and lung cancers. By pinpointing a potential novel survival signaling pathway, our data could provide a new potential therapeutic target for lung cancer treatment and management.